Construction a map of geochemical anomalies for the predicted value of gold in the Lidin ore field of Urup Island - Yuri M. Panasenko; Vladimir E. Markov; Elena V. Karelina (RUDN Journal of Engineering Research, 2021)
The purpose of this article is to study the methods of constructing maps of geochemical anomalies using geostatistical methods. The example presented in the article shows the possibility of probabilistic determination of gold in strongly overlapped areas (Urup Island, Kuril Islands). On the site of the Kolenchaty Lidinskoye ore field, the gold ore occurrence of the Kolenchaty is known. It is timed to the incision of the river and disappears outside of it. This is due to the strong overlap of the area by Quaternary sediments. Together with the uneven distribution of gold, these circumstances complicate the construction of maps of geochemical anomalies and the identification of promising areas. To solve this problem, the Statistica program was used. With its help, a matrix of correlations was built, elements of the satellites of gold were selected, and a multiple regression equation for gold was drawn up. This equation was used to probabilistically calculate gold values at each sampling point. In ArcGis, Geostatistical Analyst, geochemical anomalies were mapped from the predicted gold value by kriging, and promising areas were highlighted.